PROPAGATION OF AXISYMMETRIC WAVES IN AN INITIALLY TWISTED CIRCULAR COMPOUND BIMATERIAL CYLINDER WITH A SOFT INNER AND A STIFF OUTER CONSTITUENTS - Akbarov, S. D.; Guliev, M. S.; Kepceler, T. (SPRINGER, 2011)
Within the scope of a piecewise homogeneous body model, with the use of the three-dimensional linearized theory of propagation of elastic waves in an initially stressed body, the problem on the propagation of axisymmetric waves in an initially twisted circular compound bimaterial cylinder is studied. A mathematical formulation of the problem is presented, and the corresponding solution method is proposed and employed. Numerical results are presented and discussed for the case where the material of the outer cylinder is stiffer than the inner solid one. In particular, it is established that, as a result of initial twisting of the compound cylinder, new axisymmetric wave modes appear in it.
Keywords: initial stress; initial twisting; wave propagation; dispersion; bimaterial; circular compound cylinder; Mechanics; Materials Science; Polymer Science